Modulação dos receptores 5-HT1A e 5-HT2C DO complexo amigdalóide sobre os efeitos da fluoxetina na antinocicepção induzida pelo confinamento de camundongos aos braços do labirinto em cruz elevado - Tavares, Ligia Renata Rodrigues (Universidade Federal de São Carlos, 2016)
Previous studies have implicated the 5HT1A and 5HT2C serotonin receptors subtypes located within the amygdala in the modulation of defensive behaviors in rodents exposed to the elevated plus-maze (EPM). Further studies have shown that exposure to a threatening stimulus can result in pain inhibition. This study evaluated the effects of intra-amygdala injections of 5HT1A and 5HT2C receptor agonists on open arms antinociception (OAA) in the EPM, and possible alterations of this response with concomitant fluoxetine treatment. Male Swiss mice received 0.1 μl intra-amygdala injections of either 5.6 or 10 nmol of 8-OHDPAT, a 5-HT1A receptor agonist, and an i.p. injection of 0.6% acetic acid, a nociceptive stimulus. After confirming the start of writhing, half of the animals in each group were confined to the OA and half to the EA of the EPM, to record the number of writhes during a five-minute period (Experiment 1) A similar experimental protocol was repeated in the experiments described below. Subsequently, the animals received combined injections of fluoxetine (2.5mg/kg) and 10 nmol of 8-OHDPAT (Experiment 2). In Experiment 3, the animals received injections of either 0.21 or 0.63 nmol of MK-212, a 5-HT2C receptor agonist, and combined injections of fluoxetine (2.5mg/kg) and 0.63 nmol of MK-212 (Experiment 4). Our results showed that intra-amygdala infusions of 8-OH-DPAT enhanced nociception in both arms. Combined administration of fluoxetine and 8-OH-DPAT did not alter the observed effects. Injection of MK-212 increased the OAA, while combined administration of fluoxetine and MK-212 reversed the increase in OAA observed with MK-212 injection. These findings suggest that OAA is mediated by 5-HT2C and 5-HT1A receptors located in the amygdala. Fluoxetine interacted with 5-HT2C receptors, blocking the increase of OAA induced by activation of this serotonin receptor subtype.
Keywords: Antinocicepção; Serotonina; Fluoxetina; Amígdala; Camundongos; Antinociception; Elevated plus-maze; Serotonin; Fluoxetine; Amygdala; Mice; CIENCIAS BIOLOGICAS